The Influence of Employee Involvement and Organizational Culture on the Motivation of Civil Servants at the Department of Transportation of Kubu Raya Regency - Pratiwi, Siska; Mahdi, Irfan (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study is to analyze the influence of employee involvement and organizational culture on the work motivation of Civil Servants at the Department of Transportation of Kubu Raya Regency. This research uses an associative quantitative approach with a population of 43 civil servants selected using a saturated sampling technique. Data collection was carried out through questionnaire distribution and interviews. Instrument testing was conducted using a product moment validity test and Cronbach’s Alpha reliability test. Classical assumption tests include normality, linearity, and multicollinearity tests. The results of the regression analysis show that employee involvement and organizational culture have a positive and significant influence on work motivation, both simultaneously and partially. This is evidenced by the F-test with an F-count value of 102.367, which is greater than the F-table value of 3.23, indicating that both variables together have a significant influence. Partially, the t-test shows that employee involvement and organizational culture each have a positive and significant effect on work motivation. The correlation coefficient (R) value of 0.915 indicates a very strong relationship with a coefficient of determination (R²) of 83.7%. In conclusion, increasing employee involvement and strengthening organizational culture can be strategies to motivate employees. The practical implication is that the Department of Transportation needs to strengthen the internalization of cultural values through continuous socialization. Future research is suggested to explore other variables such as leadership or work environment that may affect motivation in the public sector.